Carbon stocks and greenhouse gas emissions (CH4 and N2O) in mangroves with different vegetation assemblies in the central coastal plain of Veracruz Mexico (2020)
The aim of this study was to quantify carbon stocks and the emission of the greenhouse gases (N2O and CH4) in mangrove forests with different vegetation assemblies in coastal lagoons of Veracruz Mexico. The vegetation included: black mangrove BM, dominated by Avicennia germinans, white mangrove WM, dominated by Laguncularia. racemose, red mangrove RM, dominated by Rhizophora mangle and mixed mangrove MM, dominated by the three species. Soil C stocks ranged 187–671 Mg C ha 1 without significant (p = 0.149) differences among the mangroves with different vegetation. Significantly (p = 0.049) higher tree biomass C stock was observed in RM (127 Mg ha−1) than in MM (24.23 Mg ha−1). Methane emissions in RM (0.58–6.03 mg m−2 min−1) were significantly higher (p < 0.05) than in MM. (0.0035–0.07 mg m−2 min−1), in WM (−0.0026–0.029 mg m−2 min−1) and in BM (0.0054–0.0097 mg m−2 min−1),during rainy, windy and dry season.RM had the longest period of inundation, the highest soil carbon concentration, and the lowest salinity. CH4 emissions showed a significantly positive correlation with soils carbon concentration, water level and water pH and, negative correlation with water salinity and Cl−1 concentration in soil and water. Emissions of N2O (0.04–3.25 μg m−2 min−1) were not significantly different among the mangroves with different vegetation, but they showed seasonal variations, with higher emissions during windy and dry seasons. N2O emissions showed significantly positive correlations with soil nitrate concentration and soil temperature. Results of this research are useful for mangrove conservation and restoration strategies to maximize carbon storage and mitigate greenhouse gas emissions.